2005
DOI: 10.1248/bpb.28.797
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-phenoxazine-3-one Attenuates Glucose-Induced Augmentation of Embryonic Form of Myosin Heavy Chain, Endothelin-1 and Plasminogen Activator Inhibitor-1 in Human Umbilical Vein Endothelial Cells

Abstract: The aim of this study was to investigate the changes in mRNA level of embryonic form of myosin heavy chain (SMemb), endothelin-1 (ET-1) and plasminogen activator inhibitor-1 (PAI-1), which are considered to be involved in the angiogenesis and atherosclerosis in diabetic blood vessels, in human umbilical vein endothelial cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…31) Phx-3 and Phx-1 are synthesized by the biological reactions of o -aminophenol or 2-amino-5-methylphenol with bovine hemoglobin solution or bovine erythrocytes, conform to the oxidative form, as Actinomycin D, and are relatively water-soluble. 20,21,32,33) Phx-3 is identical to questiomycin A that was identified as an antibiotic against Mycobacterium tuberculosis in a streptomyces isolated from the soil in Tokyo in 1959 34) and has recently been characterized as exhibiting anticancer activity against several cancer cell lines, 24,32,33) strong antimicrobial activity against Helicobacter pylori , in vitro , 35) anti-angiogenic activity indicated by the inhibition of the expression of angiogenic factors in HUVEC treated with high concentrations of glucose, 36) and anti-inflammatory activity. 37) Phx-1 has been characterized as exerting antiviral effects against poliovirus and porcine parvovirus, 38) and antimicrobial effects against Clamydia pneumoniae , 39) along with anticancer activity against several cancer cell lines, with less efficacy than Phx-3, 26) but with far higher efficacy when treated with tumor necrosis factor-related apoptosis inducing ligand (TRAIL).…”
Section: Discussionmentioning
confidence: 99%
“…31) Phx-3 and Phx-1 are synthesized by the biological reactions of o -aminophenol or 2-amino-5-methylphenol with bovine hemoglobin solution or bovine erythrocytes, conform to the oxidative form, as Actinomycin D, and are relatively water-soluble. 20,21,32,33) Phx-3 is identical to questiomycin A that was identified as an antibiotic against Mycobacterium tuberculosis in a streptomyces isolated from the soil in Tokyo in 1959 34) and has recently been characterized as exhibiting anticancer activity against several cancer cell lines, 24,32,33) strong antimicrobial activity against Helicobacter pylori , in vitro , 35) anti-angiogenic activity indicated by the inhibition of the expression of angiogenic factors in HUVEC treated with high concentrations of glucose, 36) and anti-inflammatory activity. 37) Phx-1 has been characterized as exerting antiviral effects against poliovirus and porcine parvovirus, 38) and antimicrobial effects against Clamydia pneumoniae , 39) along with anticancer activity against several cancer cell lines, with less efficacy than Phx-3, 26) but with far higher efficacy when treated with tumor necrosis factor-related apoptosis inducing ligand (TRAIL).…”
Section: Discussionmentioning
confidence: 99%
“…26,27) We reported that the SMemb level increased in HUVECs cultured in a high concentration of glucose. 28) SMemb then may be related to the dedifferentiation and vascular remodeling in diabetic atherosclerosis. In this study, we have first shown that KLF5 inhibition reduces SMemb expression not only in smooth muscle cells but also in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for few adverse effects of Phx-1 and Phx-3 should await further investigation, though the various biological effects of Phx-1 and Phx-3 including antitumor activities, immunosuppressive effects and antiviral effects etc. [17][18][19][20] have been recently reported.…”
Section: Discussionmentioning
confidence: 99%